Pengembangan Instrumen Penilaian Kemampuan Berpikir Kritis Siswa SMA - Hasan, Sri Wahyuni; Auliah, Army; Herawati, Netti (Program Pasca Sarjana UNM, 2020)
The type of this study is Research and Development (R&D) which aims at examining the development procedure and quality of assessment instruments to measure critical thinking skills of students on Stoichiometry material. The study employed Plomp’s research and development model design that consisted of 5 stages, namely: (1) initial investigation stage, consisted of field study and review literature (2) design stage, consisted of planning and organizing assessment instruments for critical thinking skills on Stoichiometry material (3) realization/ construction stage, (4) test, evaluation and revision stage, consisted of two main activities, namely validation by experts and small grub test, and (5) implementation stage is the field test. The assessment instruments which was developed was in a form of essays format. The research subjects were students of grade XI MIPA 6 SMAN at SMA N 1 Makassar with 34 students. Data on the results of the instrument’s validation by Experts was declared to be very feasible/ valid with an average percentage of 91.66%. The results of the validity analysis of the items indicate that the items support the validity of the test so that it is said to be feasible or valid, while the item reliability was stated reliable with a reliability value of 0.897 with a high interpretation. Analysis of the difficulty level of the instrument obtained an average score of 0.64 with the medium category. The distinguishing power of the instrument shows good category with an average value of 0.49. The practicality of the instruments assessed by the teacher obtained a percentage of 92.5% with a very practical category. The results of the analysis of students' critical thinking skills obtained that the average critical thinking skills of students are in medium category.